Inflammatory profile of vertically HIV-1 infected adolescents receiving ART in Cameroon: a contribution toward optimal pediatric HIV control strategies - Ka’e, Aude Christelle; Nanfack, Aubin Joseph; Ambada, Georgia; Santoro, Maria Mercedes; Takou, Desire; Semengue, Ezechiel Ngoufack Jagni; Nka, Alex Durand; Bala, Marie Laure Mpouel; Endougou, Orphelie Ndoh; Elong, Elise; Beloumou, Grace; Djupsa, Sandrine; et al. (Frontiers in Immunology, 2023)
Antiretroviral therapy (ART) has improved the lifespan of people living with HIV. However, their immune system remains in a state of sustained activation/inflammation, which favors viral replication and depletion of helper T-cells, with varying profiles according to ARTresponse. We herein sought to ascertain the inflammatory profile of adolescents living with perinatal HIV-1 infection (ALPHI) receiving ART in an African context. In this cross-sectional and comparative study among ART-experienced ALPHI in Yaoundé-Cameroon, HIV-1 RNA was measured by Abbott Real-time PCR; CD4 cells were enumerated using flow cytometry; serum cytokines were measured by ELISA; HIV-1 proviral DNA was genotyped by Sangersequencing and archived drug resistance mutations (ADRMs) were interpreted using Stanford HIVdb.v9.0.1. Overall, 73 adolescents were enrolled (60 ALPHI and 13 HIV-1 negative peers) aged 15 [13-18] years; 60.00% were female. ART median duration was 92 months; median viral load was 3.99 [3.17-4.66] RNA Log10 (copies)/mL and median CD4 count was 326 [201-654] cells/mm 3 . As compared to HIV-negative adolescents, TNFα was highly expressed among ALPHI (p<0.01). Following virological response, inflammatory cytokines (IFNγ and IL-12), anti-inflammatory cytokines (IL-4 and IL-10) and inflammation-related cytokine (IL-6, IL-1β) were highly expressed with viral suppression (VS) vs. virological failure (VF), while the chemokine CCL3 was highly expressed with VF (p<0.01). Regarding immune response, the inflammatory cytokine TNFα was highly expressed in immunocompetent (CD4≥500 cell/mm 3 ) vs. immunocompromised (CD4<500 cell/mm 3 ), p≤0.01; while chemokine CCL2 was highly expressed in immunocompromised (p<0.05). In the presence of ADRMs, IL-4 and CCL3 were highly expressed (p=0.027 and p=0.043 respectively). Among ART-experienced ALPHI in Cameroon, TNFα cytokine was found to be an inflammatory marker of HIV infection; IFNγ, IL-1β, IL-6, and IL-12 are potential immunological markers of VS and targeting these cytokines in addition to antiretroviral drugs may improve management. Moreover, CCL3 and CCL2 are possible predictors of VF and/or immunocompromised and could serve as surrogates of poor ART response.